Predicting the ductile failure of Al5083-H116 specimens with a mechanistic model and no free fitting parameters. (1st May 2017) - Bomarito, G.F.; Warner, D.H.
Abstract: A mechanistic model that does not depend on free fitting parameters was developed for predicting the ductile failure of Al 5083-H116. The model takes three inputs: (1) the large deformation constitutive response of the matrix, (2) the initial second phase particle fraction, and (3) the average nearest neighbor spacing of second phase particles. Using these inputs, a micro-scale cell model consisting of a spherical void inside a rectangular prismatic matrix was constructed. The mechanical response of the cell was simulated and cataloged, examining approximately 3000 distinct loading paths using a large deformation finite element approach. A homogenized material model was then calibrated to mimic the response of the cell across the range of stress states that were examined. Finally, the homogenized material model was used with a component-scale finite element approach to model the ductile failure of laboratory specimens having various geometries. As a whole, the hierarchical multiscale model was found to predict macroscopic failure initiation to within 25% of values measured in laboratory tests spanning a wide range of stress states. The performance of the model is compared to other common phenomenological models at both the component- and micro-scale.